2022
DOI: 10.1093/aob/mcac042
|View full text |Cite
|
Sign up to set email alerts
|

Leaf surface traits contributing to wettability, water interception and uptake of above-ground water sources in shrubs of Patagonian arid ecosystems

Abstract: Background and Aims The eco-hydrological significance of leaf wetting due to atmospheric water in arid and semiarid ecosystems is not well understood. In these environments, the inputs of precipitation or dew formation resulting in leaf wetting have positive effects on plant functioning. However, its impact on plant water relations may depend on the degree of leaf surface wettability. In this study we evaluated leaf wettability and other leaf traits and its effects on foliar water uptake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Leaf wettability is another crucial factor affecting FWU (Ali et al, 2022;Azad et al, 2015;Eller et al, 2013;Goldsmith et al, 2013;Gotsch et al, 2014;Gürsoy et al, 2017). It is substantially determined by the water-repellency of leaf surfaces, which is increased by the presence of thick cuticles, cuticle chemical properties, waxes, and glabrous surfaces (e.g., Cavallaro et al, 2022;Kupper et al, 2006;Roth-Nebelsick et al, 2022), while trichomes may decrease or increase the wettability of leaves (Fernández et al, 2014(Fernández et al, , 2017Pan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf wettability is another crucial factor affecting FWU (Ali et al, 2022;Azad et al, 2015;Eller et al, 2013;Goldsmith et al, 2013;Gotsch et al, 2014;Gürsoy et al, 2017). It is substantially determined by the water-repellency of leaf surfaces, which is increased by the presence of thick cuticles, cuticle chemical properties, waxes, and glabrous surfaces (e.g., Cavallaro et al, 2022;Kupper et al, 2006;Roth-Nebelsick et al, 2022), while trichomes may decrease or increase the wettability of leaves (Fernández et al, 2014(Fernández et al, , 2017Pan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The large variability in data was shown in Figure 5 with generally increasing standard errors of the mean leaf inclination angles after the increasing number of drop impacts on the leaf surface. This finding may express the role of accumulated water following each drop impact on the differences in leaf morphology for each leaf sample (Cavallaro et al, 2022; Koch et al, 2008; Ou et al, 2023). As expected, as drop size increased, the variability of leaf inclination angles generally increased.…”
Section: Discussionmentioning
confidence: 96%
“…Leaf surface storage is the maximum amount of water retained on a leaf divided by the all‐sided surface area of the leaf (Holder, 2013). The water contributing to leaf surface storage can be lost to evaporation, absorbed into the leaf, or contribute to throughfall or stemflow as the smaller water drops on leaf surfaces coalesce to form larger water drops and move off the leaf (Cavallaro et al, 2022; Lenz et al, 2022; Nanko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have argued that high wettability can negatively affect the plant function (e.g., increase pathogen establishment and reduce CO2 diffusion), such that wet environment should be select for less wettable leaves (Sase et al, 2008). Whereas a global analysis (Goldsmith et al, 2017) found low leaf wettability only in environment with low precipitation, recently, Cavallaro et al (2022) showed that Patagonian steppe species are highly wettable.…”
Section: Introductionmentioning
confidence: 99%